IMPLEMENTASI PERATURAN PRESIDEN NOMOR 21 TAHUN 2016 TENTANG BEBAS VISA KUNJUNGAN TERHADAP PENGAWASAN WARGA NEGARA ASING DI SUMATERA BARAT - Ilham Suriadil; Emilda Firdaus; Ledy Diana (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Visit visa free has a positive impact on increasing foreign tourists to West Sumatra in the tourism sector. The granting of a visit visa-free can be interpreted as freeing the recipients of a visit-free visa from the obligation to have a visit visa to enter Indonesian territory. The visit visa-free arrangement is expected to increase the number of foreign tourist visits to Indonesia so that it will have an effect on increasing state revenues, as well as advancing the nation's welfare. However, in reality this policy creates problems, namely the implementation of visit visas is widely misused. And the next problem is the lack of human resources on the part of immigration in carrying out supervision. The objectives in writing this thesis are: First, to find out in the application of Presidential Regulation Number 21 of 2016 concerning Visa-Free Visits, whether it is in line with the government's expectations. Second: find out what efforts have been made by related parties under the supervision of foreign nationals in misusing Presidential Regulation Number 21 of 2016 concerning visa-free visits in the province of West Sumatra. The type of research used is sociological juridical, namely research conducted by identifying the law and how the effectiveness of the implementation of the law applies in society. Because in this study the authors directly conducted research at the location or place under study to provide a complete and clear description of the problem under study. From the results of the study, it was found that the Implementation of Presidential Regulation Number 21 of 2016 concerning Visa-Free Visits to Supervision of Foreign Citizens in the West Sumatra region has not been maximized in its implementation because it will indirectly reduce non-Tax state income from the sector of purchasing visas by foreigners. The visit visa-free policy is also considered to add to TPI Padang's Class I Immigration work which basically lacks Human Resources to carry out surveillance of foreigners in the quite extensive area of West Sumatra. Immigration Control against foreigners carried out with involving relevant agencies in the field of supervision foreigners like establishment The foreigner monitoring team (TIMPORA) which Its members consist of immigration, police, prosecutors, tourism office, employment agency, BIN, BNN and agencies or institutions that have direct contact with foreigners. Author's suggestion, First, there is a need for an assessment of the policy Presidential Regulation Number 21 of 2016 regarding visa-free visits which are considered to have a threatening impact on state security. Second Increase the ability of resources officers not only in terms of quantity but also quality.